Posted by Jill on Sunday, May 15, 2011 at 2:10pm.
I will show you the first problem to give you an idea how to approach proving trig identities.
Here are a few basic identities that will help:
sinx/cosx = tanx
secx = 1/cosx
cos^2x + sin^2x = 1
Let's put everything into sine and cosine form and work the left hand side:
(secx - cosx)/tanx = sinx
(1/cosx - cosx)/(sinx/cosx) = sinx
(1/cosx - cosx)(cosx)/sinx = sinx
(cosx/cosx - cos^2x)/sinx = sinx
(1 - cos^2x)/sinx = sinx
sin^2x/sinx = sinx
sinx = sinx
And there you have it!